Clonal status and clinicopathological observation of cervical minimal deviation adenocarcinoma - Lan Miao; Zhu Shao-Jun; Yao Li; Han Xiu-Juan; Liu Xiao-Yan; Zhang Wen-Dong; Gong Li; Li Yan-Hong; Zhang Wei (BMC, 2010)
Abstract Background Minimal deviation adenocarcinoma (MDA) of the uterine cervix is defined as an extremely well differentiated variant of cervical adenocarcinoma, with well-formed glands that resemble benign glands but show distinct nuclear anaplasia or evidence of stromal invasion. Thus, MDA is difficult to differentiate from other cervical hyperplastic lesions. Monoclonality is a major characteristic of most tumors, whereas normal tissue and reactive hyperplasia are polyclonal. Methods The clinicopathological features and clonality of MDA were investigated using laser microdissection and a clonality assay based on the polymorphism of androgen receptor (AR) and X-chromosomal inactivation mosaicism in female somatic tissues. Results The results demonstrated that the glands were positive for CEA, Ki-67, and p53 and negative for estrogen receptor (ER), progesterone receptor (PR), and high-risk human papilloma virus (HPV) DNA. The index of proliferation for Ki-67 was more than 50%. However, the stromal cells were positive for ER, PR, vimentin, and SM-actin. The clonal assay showed that MDA was monoclonal. Thus, our findings indicate that MDA is a true neoplasm but is not associated with high-risk HPV. Conclusions Diagnosis of MDA depends mainly on its clinical manifestations, the pathological feature that MDA glands are located deeper than the lower level of normal endocervical glands, and immunostaining.